NLRX1 Regulation Following Acute Mitochondrial Injury - Chu, Xiaogang; Wu, Songwei; Raju, Raghavan (Frontiers in Immunology, 2019)
Several metabolic, cardiovascular and neurological disorders are characterized by mitochondrial dysfunction followed by dysregulation of cellular energetics. Mitochondria play an important role in ATP production and cell death regulation. NLRX1, a mitochondria-targeted protein, is known to negatively regulate innate immunity and cell death responses. However, the role of this protein in cellular homeostasis following mitochondrial injury is not well understood. To understand the mechanisms underlying the effect of acute injury in regulating NLRX1 signaling pathways, we used an in vitro model of mitochondrial injury wherein, rat pulmonary microvascular endothelial cells were subjected to sodium azide treatment or glucose starvation. Both sodium azide and glucose starvation activated NF/κB and TBK1 associated innate immune response. Moreover, increased TBK1, IKK, IκB and TRAF6 were recruited to mitochondria and interacted with NLRX1. Depletion of endogenous NLRX1 resulted in exacerbated NF/κB and TBK1 associated innate immune response and apoptosis. Our results suggest that NLRX1 participates in the regulation of innate immune response in mitochondria, and plays an important role in the maintenance of cellular homeostasis following acute mitochondrial injury. We propose that the mitochondrial recruitment of inflammatory mediators and their interaction with NLRX1 are protective responses to maintain cellular homeostasis following injury.